2007
DOI: 10.1148/radiol.2441060004
|View full text |Cite
|
Sign up to set email alerts
|

Does Two-Segment Image Reconstruction at 64-Section CT Coronary Angiography Improve Image Quality and Diagnostic Accuracy?

Abstract: At heart rates of more than 65 beats per minute, use of two-segment reconstruction improves image quality at multidetector CT coronary angiography but does not significantly affect overall diagnostic accuracy compared with single-segment reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…To date, no ''upper bound'' on the acceptable temporal resolution has been established. Motion artifact can also be mitigated by multisegment reconstruction [41,42]. The effective temporal resolution is halved in 2 segment (2R-R) reconstruction; the same CT volume is acquired from two heartbeats to halve the contribution from each.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no ''upper bound'' on the acceptable temporal resolution has been established. Motion artifact can also be mitigated by multisegment reconstruction [41,42]. The effective temporal resolution is halved in 2 segment (2R-R) reconstruction; the same CT volume is acquired from two heartbeats to halve the contribution from each.…”
Section: Discussionmentioning
confidence: 99%
“…In the 37 patients, a total of 474 segments was evaluated (81 segments were not included in the analysis because of anatomical variants or were less than 1.5 mm in diameter at their origin). In these 474 segments, image quality was considered as excellent in 162 (34.2%), good in 247 24.5±17.1 (0-60) Z-Axis length (cm) b 14 (12)(13)(14) Data are means±standard deviations. a Data are numbers of patients.…”
Section: Resultsmentioning
confidence: 99%
“…d ECG recording made during data acquisition cited for reduced image quality in 320-detector CTCA was motion artefact [13]. The motion artefact can be reduced by multi-segment reconstruction [24]. The effective temporal resolution is increased in 2-or 3-segment reconstruction, at the cost of significantly increased patient dose due to the longer radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The literature [6,[25][26][27] is conflicting about the potential improvements in image quality from coronary CT angiography associated with the use of multi-versus single-segment reconstruction. Herzog et al [28] found that the improved temporal resolution of two-segment image reconstruction translated into better image quality with 64-section coronary CT angiography at certain heart rates but did not improve overall diagnostic accuracy in a clinical population with a broad diversity of heart rates.…”
Section: Study Limitationsmentioning
confidence: 99%